Monocyte count to high-density lipoprotein cholesterol ratio may be a predictor in ascending aortic aneurysm (Annals of Medical Research, 2021)
Aim: The predictive value of the monocytes count and HDL-cholesterol ratio (MHR) has been demonstrated in several cardiovascular diseases. Ascending aortic aneurysm (AAA) is an important cause of mortality in adults. The aim of our study was to investigate the relationship between MHR and AAA in patients with hypertension. Material and Methods: 240 consecutive patients with AAA and 240 consecutive patients with normal ascending aortic diameter were recruited into the study by comprehensive transthoracic echocardiography. All data and MHR was compered between two groups.Results: MHR levels were significantly higher in AAA group compared to normal ascending aortic diameter group (p0.001). Higher levels of MHR was found significantly and independently associated with the AAA (p0.001). Also there was significant positive correlation between the diameter of the ascending aorta and the MHR (p0.017).Conclusion: MHR as a marker of chronic low-grade inflammation may play a role in the pathogenesis of aneurysm of the ascending aorta.
Keywords: Ascending aortic aneurysm; inflammation; monocyte/HDL ratio